2021
DOI: 10.21037/qims-20-1321
|View full text |Cite
|
Sign up to set email alerts
|

Speed of sound and shear wave speed for calf soft tissue composition and nonlinearity assessment

Abstract: Background: The purpose of this study was threefold: (I) to study the correlation of speed-of-sound (SoS) and shear-wave-speed (SWS) ultrasound (US) in the gastrocnemius muscle, (II) to use reproducible tissue compression to characterize tissue nonlinearity effects, and (III) to compare the potential of SoS and SWS for tissue composition assessment.Methods: Twenty gastrocnemius muscles of 10 healthy young subjects (age range, 23-34 years, two females and eight males) were prospectively examined with both clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…This study and many other studies support the theory that pressure on soft tissue changes its shear-wave speed measurement [ 11 , 12 , 13 , 14 , 15 ]. The raw results showed that even when minimal pressure is applied, there are still changes in the measured speed due to the placement of the probe.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This study and many other studies support the theory that pressure on soft tissue changes its shear-wave speed measurement [ 11 , 12 , 13 , 14 , 15 ]. The raw results showed that even when minimal pressure is applied, there are still changes in the measured speed due to the placement of the probe.…”
Section: Discussionsupporting
confidence: 88%
“…The nonlinear behaviour of tissue causes errors in the measurements made since, in most clinical settings, the pressure from ultrasound probes is unregulated. This phenomenon, known as “tissue stiffening” or “strain stiffening”, is present in most soft tissues, for example, breast tissue [ 11 ], heel pad [ 12 , 13 ], calf muscle [ 14 ] and thyroid gland [ 15 ]. The occurrence of tissue stiffening is especially detrimental for cervical elastography as the probe is in direct contact with the tissue, and the shape of the probe causes non-uniform deformation [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, shear and longitudinal waves interrogate fundamentally different mechanical tissue properties [28]. Their propagation velocities differ by three orders of magnitude, resulting in decoupled relationships between the two velocities and elastic moduli [31]. Hence, our work not only complements other studies on the topic but is pivotal to characterize mechanical tissue properties comprehensively.…”
Section: Discussionmentioning
confidence: 73%
“…Such a medium is characterized by five independent elastic parameters, describing, for instance, the longitudinal-and shear-wave velocities along and across the symmetry axis. In soft tissue, however, shear-wave velocities are negligible in comparison to longitudinal-wave velocities [31]. Therefore, it is possible to describe muscle properties using only three independent parameters.…”
Section: Traveltime Modelling In Anisotropic Mediamentioning
confidence: 99%
See 1 more Smart Citation